2021
DOI: 10.1038/s41593-021-00975-6
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 interacts with TDP-43 and mediates microglial neuroprotection against TDP-43-related neurodegeneration

Abstract: Triggering receptor expressed on myeloid cell 2 (TREM2) is a surface receptor that, in the central nervous system, is exclusively expressed on microglia. TREM2 variants have been linked to increased risk for neurodegenerative diseases, but the functional effects of microglial TREM2 remain largely unknown. To this end, we investigated TAR-DNA binding protein 43 kDa (TDP-43)-related neurodegenerative disease via viral-mediated expression of human TDP-43 protein (hTDP-43) in neonatal and adult mice or inducible e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 82 publications
2
79
0
Order By: Relevance
“…Increasing sTREM2 in the CNS has been reported to trigger microglia activation, promote microglia survival, and ameliorate pathological phenotypes (Zhong et al, 2017(Zhong et al, , 2019. Our studies revealed a potential role of sTREM2 in TDP-43 clearance in ALS (Xie et al, 2022). In addition, sTREM2 has been reported to be present on neuronal soma in both cortex and hippocampus of AD mice (Song et al, 2018), suggesting a potential role in removing apoptotic neuronal cells.…”
Section: Future Directionsmentioning
confidence: 50%
See 4 more Smart Citations
“…Increasing sTREM2 in the CNS has been reported to trigger microglia activation, promote microglia survival, and ameliorate pathological phenotypes (Zhong et al, 2017(Zhong et al, , 2019. Our studies revealed a potential role of sTREM2 in TDP-43 clearance in ALS (Xie et al, 2022). In addition, sTREM2 has been reported to be present on neuronal soma in both cortex and hippocampus of AD mice (Song et al, 2018), suggesting a potential role in removing apoptotic neuronal cells.…”
Section: Future Directionsmentioning
confidence: 50%
“…Our findings revealed a protective function of microglial TREM2 during ALS progression (Xie et al, 2022), thus increasing microglial TREM2 activity or expression at certain disease stages may alleviate ALS-related dysfunctions. To achieve this, pharmacological intervention or gene therapies, such as antisense oligonucleotides (ASOs), could be applied.…”
Section: Targeting Trem2 To Treat Alsmentioning
confidence: 64%
See 3 more Smart Citations